2010
DOI: 10.1007/s00432-010-0803-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of bevacizumab on serum soluble FAS/FASL and TRAIL and its receptors (DR4 and DR5) in metastatic colorectal cancer

Abstract: Non-significant changes in apoptotic markers with bevacizumab-based chemotherapy showed that they have no prognostic significance in MCRC patients. Significant change in sFAS/sFASL ratio according to treatment response could be an indicator of chemosensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Furthermore, FAS signaling promotes COAD metastasis through inducing epithelial-mesenchymal transition (Chen et al, 2017). The significant change of sFAS/sFASL ratio from metastatic COAD treatment response might be an indicator of chemosensitivity (Yildiz et al, 2010). FAS resisted the apoptosis of metastatic COAD cells by participating in the adjustment of its gene products (Huerta et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, FAS signaling promotes COAD metastasis through inducing epithelial-mesenchymal transition (Chen et al, 2017). The significant change of sFAS/sFASL ratio from metastatic COAD treatment response might be an indicator of chemosensitivity (Yildiz et al, 2010). FAS resisted the apoptosis of metastatic COAD cells by participating in the adjustment of its gene products (Huerta et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Although Yildiz et al detected the expression of serum sDR5 levels in metastatic colorectal cancer, the authors did not investigate the generation of serum sDR5 (9). We propose that another important death receptor, serum sFas, may originate from the tumor tissues themselves, as a correlation between sFas/CD95 serum concentration and the patient’s stage of disease has been observed (25).…”
Section: Discussionmentioning
confidence: 99%
“…This significant change may be a result of the effect of bevacizumab on cancer cells via apoptosis. Another study has found that, although there was no significant difference between sTRAIL, soluble death receptor (sDR)4 and sDR5 levels in MCRC patients before and after treatment, significant correlations were observed between post-treatment sFASL and sDR4, post-treatment sFAS and sTRAIL, post-treatment sTRAIL and sFAS/sFASL ratio, and post-treatment sFASL and sDR5 [34]. This controversy may also have been due to the patients enrolled in the study.…”
Section: Discussionmentioning
confidence: 99%